Cartuja 98, A Technological Park located at the site of Sevilla's World's Fair - Antonio Vazquez-Barquero; Emilio Carrillo (European Regional Science Association (ERSA), 2004)
The Cartuja 93 Technological Park was created in 1993 and was located at the site of the World's Fair that took place in Sevilla in 1992. The Park's emergence and formation, between 1993 and 1999, was a slow and dificult process and during this period it was very common among social scientists to refer to it as as a failure, as the deserted Cartuja. At present, however, it seems that Cartuja 93 is consolidated and has become an urban Tecnological Park. Within Sevilla's technopolis, research and development centers, technology transfer units and high technology and advanced service firms are located. The paper describes the formation and consolidation process of Cartuja 93, analyses the changes and transformation of the technopolis and asses the results of the Technological Park.
Keywords: 330